De Argentina a España: la adaptación de la variación lingüística en el subtitulado intralingüístico de El secreto de sus ojos - Maria Nieves Jimenez Carra (JoSTrans: The Journal of Specialised Translation)
In this paper, a comparative analysis is carried out between the original and the subtitled-for-the-deaf versions of the movie El secreto de sus ojos (The Secret in their Eyes) (Campanella 2009). In this subtitling, the Argentinean Spanish of the original is adapted into the Castilian variety. This is noticed in the lexical, grammatical, or syntactic levels. The study has several aims: to analyse how the variety has been adapted, by means of examples taken from the original and the subtitled versions; to establish whether this adaptation is coherent throughout the entire target text; and to determine if the reason for this change might be related with the fact that the audience may not understand the original vocabulary, expressions or verb tenses. After some brief remarks on the relation between translation, audiovisual translation and language variation, the comparative analysis will be presented, so as to show the presence of elements belonging to the following categories: swearwords, interjections, the use of the vos form and the presence of different verb tenses, vocabulary and expressions, as well as the rare exceptions where no adaptation has been found in the subtitling. The study concludes that the Argentinean vocabulary and expressions that appear in the original text are, in most cases, understandable enough and sometimes even used by a Castilian-Spanish speaker. Consequently, a possible misunderstanding is not likely to be the reason for the elimination of the characteristics of the Argentinean variety in the intralinguistic subtitling, nor for its almost complete adaptation into the Castilian variety.